2006
DOI: 10.1124/dmd.106.009902
|View full text |Cite
|
Sign up to set email alerts
|

Selective Metabolism of Vincristine in Vitro by Cyp3a5

Abstract: ABSTRACT:Clinical outcomes of vincristine therapy, both neurotoxicity and efficacy, are unpredictable, and the reported pharmacokinetics of vincristine have considerable interindividual variability. In vitro and in vivo data support a dominant role for CYP3A enzymes in the elimination of vincristine. Consequently, genetic polymorphisms in cytochrome P450 (P450) expression may contribute to the interindividual variability in clinical response, but the contributions of individual P450s and the primary pathways o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
117
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 153 publications
(133 citation statements)
references
References 35 publications
(43 reference statements)
6
117
1
2
Order By: Relevance
“…In preliminary experiments, however, low concentrations of thalidomide did not activate the oxidative cleavage of vincristine (catalyzed by P450 3A5 or liver microsomes with CYP3A5*1/*3) (results not shown). The K m values (for the major oxidative cleavage of vincristine catalyzed by P450 3A5) have been reported to be 13 to 17 M (Dennison et al, 2006). Because vincristine is a large molecule and has high P450 3A5 affinity, these present results may be interpreted that thalidomide could not dock in P450 3A5 before vincristine.…”
Section: Discussionsupporting
confidence: 43%
“…In preliminary experiments, however, low concentrations of thalidomide did not activate the oxidative cleavage of vincristine (catalyzed by P450 3A5 or liver microsomes with CYP3A5*1/*3) (results not shown). The K m values (for the major oxidative cleavage of vincristine catalyzed by P450 3A5) have been reported to be 13 to 17 M (Dennison et al, 2006). Because vincristine is a large molecule and has high P450 3A5 affinity, these present results may be interpreted that thalidomide could not dock in P450 3A5 before vincristine.…”
Section: Discussionsupporting
confidence: 43%
“…For instance, Klees et al (2005) reported a 5-to 7-fold increase in CL int of alfentanil in CYP3A4 microsomes coexpressed with cytochrome b 5 . Furthermore, the formation of the major metabolite of vincristine through CYP3A5 was stimulated (3-fold) by the presence of coexpressed cytochrome b 5 (Dennison et al, 2006). The conflicting results indicate a substrate-dependent impact of cytochrome b 5 , and this should be further evaluated for more substrates.…”
Section: Discussionmentioning
confidence: 99%
“…The two transporters may also have substrates with mutually complementing neurotoxic effects. The routes of metabolism and the intermediary metabolites of some cytostatic drugs are not yet fully discovered, although important new data are emerging nowadays, 29 and transport properties of possibly neurotoxic metabolites of chemotherapy agents are unexplored. Such metabolites might also play a role in the consequences of interindividual differences of efflux transporter activities.…”
Section: Discussionmentioning
confidence: 99%